2021
DOI: 10.1097/scs.0000000000007787
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sex From Dental Arch Dimensions: An Odontometric Analysis

Abstract: Sex estimation is one of the ''big three'' of human identification and is a vital aspect of the process of generating biological profile of unknown deceased. Anthropometric and odontometric methods that utilize measurement of distances between certain landmarks are commonly employed to differentiate between the 2 sexes. Teeth are the most robust and well-preserved parts of the human body, and studies have shown that the sex of an unknown individual can be estimated using their measurements. The present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the only study that used these three measurements for the analysis, and their measurements found varied in males and females. A Serbian study (39) used Moorrees and Reed's method [50] to determine measurements of the canines in the present study; the authors used the Gran [22,23] method.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of the authors' knowledge, this is the only study that used these three measurements for the analysis, and their measurements found varied in males and females. A Serbian study (39) used Moorrees and Reed's method [50] to determine measurements of the canines in the present study; the authors used the Gran [22,23] method.…”
Section: Discussionmentioning
confidence: 99%
“…Sex identification has become one of the essential parameters in any forensic investigation. Teeth have been considered by the majority of the researchers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] for sex determination with the aid of odontometric analysis. The odontometric parameters offer an alternative, easy and dependable approach to sex determination [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations